2014 55th International Scientific Conference on Power and Electrical Engineering of Riga Technical University (RTUCON) 2014
DOI: 10.1109/rtucon.2014.6998194
|View full text |Cite
|
Sign up to set email alerts
|

Core-form transformer design optimization with branch and bound search and geometric programming

Abstract: The optimization of power transformers is one of the earliest applications of geometric programming. This approach works well with shell-form transformers, and the constructed models can be solved accurately with the new interior point method based solvers. However, a less well-known fact is that this kind of modeling becomes problematic in the case of core-form transformers.This paper shows a new metaheuristic solution to circumvent the main obstacle which is the calculation of short-circuit impedance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…He rejected to use the manufacturing cost as the objective function, instead of this he was proposed to use the sum of the manufacturing and the operating costs as the objective of the optimization. This phenomenon is similar to the modern lifetime cost optimization approaches [1,91,[103][104][105][106][107] (Fig. 5).…”
Section: Analytical Cost Optimization Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…He rejected to use the manufacturing cost as the objective function, instead of this he was proposed to use the sum of the manufacturing and the operating costs as the objective of the optimization. This phenomenon is similar to the modern lifetime cost optimization approaches [1,91,[103][104][105][106][107] (Fig. 5).…”
Section: Analytical Cost Optimization Methodssupporting
confidence: 74%
“…Following this axiom, the application of larger main gap increases the cost of the active part of an electrical machine. Due to the non-linearity of the electrical machine design problem this design principle does not corresponds with the practice, where the cost optimal transformers, autotransforemrs have larger main gap than the required minimum [5,8,13,14,104]. Csikos has already confuted another old design rule [103], which states that if the transformer designed for maximal efficiency it has as same load as no-load losses.…”
Section: Analytical Cost Optimization Methodsmentioning
confidence: 99%
“…These practical formulas are the results of measurements, which are made by an Epstein-apparatus and they are take the hysteresis and eddy losses into account. The applied loss function is fitted to the applied electrical steel data (M1H [45]) and approximated by a polynomial expression [9,14,27,46]:…”
Section: Core Mass and No-load Loss Calculationmentioning
confidence: 99%
“…To formulate a problem in GP format, the equality constraints shall be formulated in monomial form, and the inequalities in a special posynomial form [26]. The previous articles of the authors [24,25] have shown that the short circuit impedance cannot be formulated in either monomial nor in posynomial format properly. A solution for the problem has be shown by the combination of this method with a branch and bound search [25].…”
Section: The Geometric Programming Based Meta-heuristic Algorithmmentioning
confidence: 99%
“…Therefore in the last decades, a wide range of mathematical optimisation methods have been implemented for this design optimisation problem, such as Monte Carlo simulation [18], artificial intelligence techniques and neural networks [19], evolutionary and genetic algorithms [13][14][15][16][17][18], and geometric programming (GP) [1,20,24,25]. The importance of GP is based on the recent developments in the solution methods, which can solve even large-scale GPs extremely efficiently and accurately [26][27][28].…”
Section: Introductionmentioning
confidence: 99%